Spatial phylogenetics - Mishler, Brent D. (Journal of biogeography, 2023)
The metric called phylogenetic diversity (PD) has been employed over the last 30 years to add an evolutionary dimension to the exploration of biodiversity. However, the application of PD was until recently limited by both technology and methodology. Newly available distributional data from global museum databasing efforts, rapidly increasing coverage of DNA sequence data and improvements to computer hardware and software have enabled a new ‘big data’ approach to the application of PD‐based metrics and randomization‐based hypothesis tests called ‘spatial phylogenetics’. It can be defined most simply as turning a phylogeny into a GIS layer, which can then be used with other GIS layers to understand drivers of phylodiversity patterns and for conservation prioritization. Alpha and beta phylodiversity can be measured using different ways of representing branch lengths on a given topology (called ‘facets’), each yielding a different, interesting perspective that are best viewed in combination. Challenges posed by available data need to be addressed through careful cleaning and gathering further data in a targeted manner. Spatial phylogenetics is only in its infancy, showing much promise but with many elements awaiting expansion to address further questions.